Tratores, orquídeas e tilápias: uma análise sobre turismo e identidade em Maripá/PR - Rech, Carla Martina (2018)
This research deals with oral narratives and speeches published in newspapers and magazines aimed at building a certain picture of Maripa city, situated in the West of Paraná State. The picture was supported by identity symbol/images to promote a town´s propaganda such as: the tractor, the orchid and the tilapia fish. All symbols are erected as a portic in the road close to the town´s gateway. The first experimental fishery unit of Maripá was started at the year of 1993 and, later in 1996 the town lauched its Fish Promotion Program. The first Tractor Racing took place at the town´s avenue in 1990 and the first town´s anual Fish and Orchid Festival was started in 1998. Later in 2003 the first Tractor Racing using a proper racetrack was carried out in a place called “Tratoródromo”. This research, therefore has its historical scope limited to the temporal gap between 1990 and the present. Over the discussion we approach the speeches and literature used to produce the identity meaning in the Maripá citizens´s culture.